The characteristics of the sum of a multidimensional series - Makarov, V.Yu. (Український математичний журнал, 1994)
We study the relationship between the asymptotic behavior of coefficients of a multidimensional series of exponents and the asymptotic behavior of its sum near a point on the boundary of the domain of convergence. Growth characteristics, an order ρQ(a), and a type σQβ(a) in an octant Q(a) are determined. The dependence of growth characteristics on the coordinates of points of the boundary of the domain of convergence is established. Вивчається зв'язок асимптотичної поведінки коефіцієнтів багатовимірного ряду експонент з асимпотичною поведінкою його суми поблизу точки на межі збіжності. Визначені характеристики зростанння, порядок ρQ(a) та тип σQβ(a) в октанті Q(a). Встановлена залежність характеристик зростання від координат точок збіжності.